Tax Reform Imperative: Alleviating Financial Burden and Fostering Middle-Class Prosperity in the U.S. Economy - Kallianiotis, Ioannis (Journal of Business and Economic Options, 2022)
The paper critically examines the existing U.S. tax system, highlighting its detrimental effects on disposable income and savings behavior. The current tax structure, characterized by high individual tax rates, has resulted in negative savings rates and increased borrowing among individuals, contributing to escalating personal debt levels. Moreover, low taxation on businesses has exacerbated budget deficits and national debt, creating a significant burden on the economy. Individuals essentially borrow against their uncertain future wealth, amplifying financial risks with high debt levels and low incomes. Consequently, increased interest rates on loans, particularly on credit cards, further strain household finances. To address these challenges, the paper proposes several policy recommendations. It suggests reconsidering corporate tax rates to generate additional revenue and implementing measures to lower government expenditures, particularly in areas such as military spending. Reforming the tax system is imperative to foster social welfare, fairness, and justice within society. The burden placed on the middle class undermines their ability to accumulate wealth and maintain a satisfactory standard of living, posing a significant threat to the socio-economic fabric of the nation. Historically, the strength of societies has been closely linked to the health of the middle class. Its decline can lead to detrimental consequences for the overall economy and societal well-being. Proactive measures are needed to address the challenges facing the middle class, including tax system reform and policies that promote economic growth and opportunity. By prioritizing the interests of the middle class, leaders can help ensure greater prosperity and a more equitable society for all citizens. This paper highlights the urgent need for tax reform and fiscal policy adjustments to alleviate the financial strain on households and address broader economic challenges posed by the current tax system and fiscal imbalance.